Kinase inhibitors: Opportunities for small molecule anticancer immunotherapies. Issue 5 (May 2023) - Safaroghli-Azar, Ava; Emadi, Fatemeh; Lenjisa, Jimma; Mekonnen, Laychiluh; Wang, Shudong
Highlights: Kinase inhibitors reshape the TME to overcome tumor-associated immunosuppression. By activating innate immunity, kinase inhibitors increase tumor immunogenicity. Kinase inhibition-mediated upregulation of ICs enhances the efficacy of mAbs. By elevating TILs, kinase inhibitors can boost the efficacy of immunotherapy. Abstract : As the fifth pillar of cancer treatment, immunotherapy has dramatically changed the paradigm of therapeutic strategies by focusing on the host's immune system. In the long road of immunotherapy development, the identification of immune-modulatory effects for kinase inhibitors opened a new chapter in this therapeutic approach. These small molecule inhibitors not only directly eradicate tumors by targeting essential proteins of cell survival and proliferation but can also drive immune responses against malignant cells. This review summarizes the current standings and challenges of kinase inhibitors in immunotherapy, either as a single agent or in a combined modality.